1996
DOI: 10.1021/ac950813j
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nonaqueous Capillary Electrophoresis to the Separation of Long-Chain Surfactants

Abstract: The potential of nonaqueous capillary electrophoresis (CE) for the separation of hydrophobic solutes has been examined for a series of alkanesulfonates (C 2 -C 16 ), alkyl sulfates (C 8 -C 18 ), and linear alkyl benzenesulfonates. Sample loss and band broadening observed in aqueous CE separations was not observed in nonaqueous systems. Changes in separation selectivity induced by solvation and ion pair effects were examined. Separation selectivity was affected by changes in solvation and by a change from proti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 26 publications
3
67
1
2
Order By: Relevance
“…There have been several reports for the separation and detection of fatty acids by CE (Collet and Gareil, 1997;Koval et al, 1985;RoldanAssad and Gareil, 1995;Salimi-Moosavi and Cassidy, 1996;Schmitz and Gab, 1997;Drange and Lundanes, 1997;Erim et al, 1995;Wang et al, 1998;Wan et al, 1999). Most of the methods utilize the indirect UV absorbance detection system by adding p-methoxybenzoate (Collet and Gareil, 1997;Roldan-Assad and Gareil, 1995), p-toluenesulfonate (Salmi-Moosavi and Cassidy, 1996), anthraquinone-2-sulfonic acid (Drange and Lundanes, 1997), or dodecyl benzenesulfonate (Erim et al, 1995) as a chromophore, or utilize indirect fluorescence detection system by adding fluorescein (Wang et al, 1998) in the migration medium.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports for the separation and detection of fatty acids by CE (Collet and Gareil, 1997;Koval et al, 1985;RoldanAssad and Gareil, 1995;Salimi-Moosavi and Cassidy, 1996;Schmitz and Gab, 1997;Drange and Lundanes, 1997;Erim et al, 1995;Wang et al, 1998;Wan et al, 1999). Most of the methods utilize the indirect UV absorbance detection system by adding p-methoxybenzoate (Collet and Gareil, 1997;Roldan-Assad and Gareil, 1995), p-toluenesulfonate (Salmi-Moosavi and Cassidy, 1996), anthraquinone-2-sulfonic acid (Drange and Lundanes, 1997), or dodecyl benzenesulfonate (Erim et al, 1995) as a chromophore, or utilize indirect fluorescence detection system by adding fluorescein (Wang et al, 1998) in the migration medium.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Some researchers reported that the addition of organic solvents to the buffer solutions was effective for separation optimization of alkyl sulfates and alkane sulfonates. 9,14 We also studied the effect of addition of organic solvents on the separation of N-acyl-L-glutamates.…”
Section: Effect Of Addition Of Organic Solvents On Separationmentioning
confidence: 99%
“…14,15 Some researchers reported that the addition of organic solvents to the buffer solutions was effective for separation optimization of alkyl sulfates and alkane sulfonates. 9,14 We also studied the effect of addition of organic solvents on the separation of N-acyl-L-glutamates. In this study, methanol, as a protic solvent, and acetonitrile, as an aprotic one, were chosen as organic modifiers, because both of them possess water-miscibility in any ratios, good transmittance at low wavelength in UV region, and increase the solubility of hydrophobic analytes.…”
Section: Effect Of Addition Of Organic Solvents On Separationmentioning
confidence: 99%
“…C'est d'ailleurs une des raisons pour lesquelles le méthanol et l'acétonitrile sont les solvants les plus utilisés en milieu non aqueux. Il est cependant à signaler que d'autres modes de détection peuvent être envisagés, la détection UV indirecte [13,14], la détection fluorimétrique indirecte induite par LASER [15,16], la détection électrochimique qui est bien adaptée aux solvants dipolaires aprotiques comme le dimethylformamide, le dimethylsulfoxyde et l'acétonitrile [17][18][19] ou encore le couplage CE/MS qui nécessite des solvants volatils tels que le méthanol ou l'acétonitrile [4,[20][21][22]. Ainsi dans l'étude du métabolisme du tamoxifène en électrophorèse capillaire couplée à la spectrométrie de masse (ESI), il a été constaté une meilleure résolution et une sensibilité plus grande en milieu organique par rapport au milieu aqueux [22].…”
Section: Détectionunclassified